Stakeholder Management Practices: Case Study of Marine rehabilitation Project at Ghana Ports and Harbour authority (Takoradi Shipyard) - Charles Alampah (KNUST, 2025)
A thesis submitted to the Department of Construction Technology and Management, Kwame Nkrumah University of Science and Technology, Kumasi in Partial Fulfilment of the requirements for the Degree of Master of Science in Project Management